Jonas Aistis’ and Sigitas Geda’s Notion of Open Cultural Identity: Between Universality and National Self-Preservation - Bagdonė, Karolina (Colloquia, 2022)
In this article, author uses the theory of intertextuality to examine how the works of two Lithuanian poets, Jonas Aistis and Sigitas Geda, revised Western literary works during the Soviet era and what kind of European identity they conveyed by creating intertextual connections. Both poets during the Cold War looked for the ways to make vital links with Western literature and to continue to reflect on the relationship between Europeanness and Lithuanianness that had taken place in Lithuania before World War II. Aistis turned to the classical era that was popular in the interwar period, especially the myths of Medea, Orpheus and Eurydice, and the works of Edgar Allan Poe. Using intertexts, he reflected on the ideas of double homelessness (love for the lost Lithuania and Europe), post-catastrophic identity, and the painful disappointment with the diminished impact of his poetry. The ideas of national and European identity as a synthesis of the West and the East reflected in the works by Stasys Šalkauskis and Adomas Mickevičius, as well as Johann Wolfgang von Goethe’s vision of the universality of world literature, were important in Geda’s poetry. They were significant in creating authentic intertextual links with the works of Western literature (such as Ovid, Homer, Rainer Maria Rilke and Georg Trakl), in order to preserve the complex historical European experience and to provoke readers’ self-consciousness in opposing the repressive Soviet regime.